The status of soil phosphate fractions and the ability of fungi to dissolve hardly soluble phosphates - Barroso, C. B.; Nahas, E. (Elsevier B.V., 2005)
Brazilian soils predominantly consist of iron and aluminum oxides and have a low phosphorus content. The present study was carried out in order to assess the status of phosphate fractions in pasture, forest and agricultural soils and the ability of soil fungi to solubilize iron and aluminum phosphates. The abundance of P fractions in the soils studied occurred in the following order: Fe-P > reductant-soluble Fe-P > occluded Fe-P > occluded Al-P > Al-P > Ca-P. of the 481 fungi isolated, 33 showed the ability to solubilize the inorganic phosphates in culture. of these, 14 were considered to be high or very high solubilizers based on a solubilization capacity > 1000 mu g PO43- ml(-1). Isolate F-111 was the only one that dissolved all the insoluble phosphates used. Nine isolates solubilized both Al-P and Ca-P, and four other isolates only solubilized Ca-P. The highest number of isolates with high solubilization capacity were detected in pasture soil, followed by tropical rain forest and forest patch soils. Pasture soil presented both the largest contents of insoluble phosphates and the largest number of fungal isolates with phosphate-solubilizing ability. The range and size of P fractions influenced the number of fungi and their ability to solubilize hardly soluble phosphates. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: phosphorous fractions; phosphate solubilization; low solubility phosphate; Fungi